Can front-of-pack labels influence portion size judgements for unhealthy foods? - Talati, Zenobia; Pettigrew, Simone; Kelly, B.; Ball, K.; Neal, B.; Dixon, H.; Shilton, Trevor; Miller, C. (Cambridge University Press, 2018)
Objective: By clearly conveying the healthiness of a food, front-of-pack (FOP) labels have the potential to influence the portion size considered appropriate for consumption. The present study examined the how the Daily Intake Guide (DIG), Multiple Traffic Lights (MTL) and Health Star Rating (HSR) FOP labels affect judgements of appropriate portion sizes of unhealthy foods compared with when no FOP label is present. Design: Respondents viewed mock packages of unhealthy variations of pizzas, cookies, yoghurts and cornflakes featuring the DIG, MTL, HSR or no FOP label, and indicated the portion size they believed should be eaten of each food on a single occasion. Setting: The survey was completed on the respondent’s personal computer. Subjects: A total of 1505 Australian adults provided 4166 ratings across 192 mock packages relating to four product categories: pizza, yoghurt, cornflakes and cookies. Results: Compared with no FOP label, the HSR resulted in a small but significant reduction in the portion size selected as appropriate for consumption of pizzas and cornflakes (P<0·05). The MTL resulted in smaller portions of cornflakes being selected compared with no FOP label (P<0·05). Conclusions: Respondents perceived smaller portion sizes as appropriate for some, but not all, of the foods tested when FOP labels with more interpretative formats (HSR, MTL) appeared on-pack compared with no FOP label. No effect was found for the less interpretive FOP label (the DIG). Interpretive FOP labels may have the potential to influence portion size judgements, albeit at modest levels.